Effects of Postural Education and Physical Activity on UCLA Evaluation and Health Status in Adults from Chile: An Intervention Program - Félix Zurita-Ortega; Ramón Chacón-Cuberos; Manuel Fernández-Sánchez; Cristian Cofre-Bolados; María Concepción Navarro-Zurita; Manuel Castro-Sánchez (MDPI AG, 2018)
Shoulder pathologies among the adult population are increasing, causing a high concern in health-educational institutions. The aim of this research is to take a step further and to conduct a detailed study of the relationship between the application of Jackins technique and a postural education program for people affected by shoulder problems. This quasi-experimental study was carried out on 41 adults with shoulder pathologies, with an average age of 58.17±11.75. The main instruments used were the UCLA Test, Thermometer Euroqol of Health, and an ad-hoc questionnaire. In addition, SPSS 22.0 was used for statistical analysis. The results show that the Jackins shoulder rehabilitation program produces significant improvements in participants who it was applied to, causing a positive increase in shoulder evaluation and health status. Similarly, participants who were given a postural education treatment did not experience any modification in these variables. The Jackins program resulted in improvements in reference to shoulder evaluation. Thus, the course of the intervention program based on physical activity (six months) produces functional improvements in shoulder pathology through supervised therapeutic exercises and home intervention in patients with subacromial syndrome.